Localized positronium-like states in ionic crystals - Boev O. V. (1981, 1981)
The localized positronium-like states in ionic crystals are considered as positron-electron pair bound states in the Coulomb field of the charge Z. The system characteristics are evaluated as a function of the magnitude Z. The calculated data are in agreement with the experimental ones in alkali halides for charges Z < 0.7. The properties and the formation possibility of the positronium-like states in ionic crystals are discussed.